1994
DOI: 10.1037/0012-1649.30.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity in infants: A cross-national comparison.

Abstract: Four-month-old infants from Boston, Dublin, and Beijing were administered the same battery of visual, auditory, and olfactory stimuli to evaluate differences in level of reactivity. The Chinese infants were significantly less active, irritable, and vocal than the Boston and Dublin samples, with American infants showing the highest level of reactivity. The data suggest the possibility of temperamental differences between Caucasian and Asian infants in reactivity to stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 13 publications
3
56
1
2
Order By: Relevance
“…Third, our study indicates that service firms should be aware of the differences in the influence of employees' emotional displays on customers with different degrees of susceptibility to emotional contagion. The prior literature suggests that there is a difference in the emotional expressions between eastern and western cultures (Dickson et al 1998;Kagan et al 1994;Russell 1995). For example, Russell (1995) suggested that people from eastern countries can control their emotions better than those from western countries.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, our study indicates that service firms should be aware of the differences in the influence of employees' emotional displays on customers with different degrees of susceptibility to emotional contagion. The prior literature suggests that there is a difference in the emotional expressions between eastern and western cultures (Dickson et al 1998;Kagan et al 1994;Russell 1995). For example, Russell (1995) suggested that people from eastern countries can control their emotions better than those from western countries.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…For example, Russell (1995) suggested that people from eastern countries can control their emotions better than those from western countries. Kagan et al (1994) provided behavioral and physiological evidence that Chinese people tend to have less emotional responses than white people do. This implies that people from western cultures are more willing to display their emotions on their face, while people from eastern culture like to hide their emotions internally (Dickson et al 1998).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…It is assumed, but not yet proven, that the biological foundations for most, but certainly not all, human temperaments are heritable neurochemical profiles. This hypothesis was present in an early form in the writings of the ancient Greeks, who posited melancholic, sanguine, choleric, and phlegmatic temperaments derived from the balance of the four humors of blood, bile, phlegm, and black bile (Kagan, 1994).…”
Section: Temperaments As Sets Of Preparedness Jerome Kaganmentioning
confidence: 99%
“…It may not be a coincidence that a high-reactive temperament is far more frequent among Caucasian than among Chinese 4-month-old infants (Kagan et al, 1994). Moreover, Japanese, compared with CaucasianAmerican, infants are less easily aroused, less likely to cry during an inoculation, and less distressed by restraint of their arms (Caudill & Weinstein, 1969;Lewis, Ramsey, & Kawakami, 1993).…”
Section: High-and Low-reactive Infantsmentioning
confidence: 99%
“…There is a lot of evidence that adults and children who do not have ASD will engage in mimicking [13], [14], [15] and we would like to find out whether there is a difference in the mimicking behavior of typically developing and autistic children in a game setting, where expressing emotions and establishing an emotional connection are natural. We initially intended to investigate the differences in unconscious mimicry (Chameleon Effect) by autistic and typically developing children, but there might be an effect of on-purpose mimicry (e.g.…”
Section: Introductionmentioning
confidence: 99%